Metabolic Syndrome in Children with Overweight and Obesity - Elmoctar, Sidina Mohamed; Salah, Dhoha Ben; Elleuch, Mouna; Ahmed, Mohamed Abdellahi Mohamed; Khouloud, Boujelban; Mnif, Mouna; Mnif, Fatma; ReKik, Nabila; Nadia, Charfi; Faten, Hadj Kacem; et al. (British Journal of Healthcare and Medical Research, 2022)
Background: While many studies have been conducted on the prevalence and complications of metabolic syndrome in adults, few pediatric studies are available, particularly in developing countries. The aim of this study is to determine the prevalence of metabolic syndrome and its components among children and adolescents with overweight and obesity in Sfax, Tunisia. as well as to look for predictive factors for the occurrence of this pathology. Methods: This cross-sectional study involved 84 children and adolescents with overweight and obesity admitted to the endocrinology department of Hédi Chaker Hospital, Sfax from 2015 to 2019. For each participant included in the study, a clinical examination was conducted to determine height (cm), weight (kg), waist circumference (cm), and BMI as weight/height² (kg/m2). A fasting blood sample was taken to assay the different biological parameters. Results: Between 44 boys and 40 girls, the average age was 11.83 years. Family history of obesity was noted in 84.5% of cases. The average weight was 72.68 kg, with an average BMI of 31.55 kg/m². Obesity was reported in 78.6% of patients and overweight without obesity in 21.4%. According to adapted NCEP/ATP III criteria, 16.7% of patients had metabolic syndrome. Metabolic syndrome was observed in 15.9% of boys and 17.5% of girls, with no significant difference. In our study, no predictive factors were found. Conclusion: The prevalence of metabolic syndrome was high in our study. We suggest targeted screening programs for at-risk children and adolescents to control obesity and metabolic syndrome in Tunisia.